2001
DOI: 10.1073/pnas.98.3.926
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a quinone reductase activity for the mitomycin C binding protein (MRD): Functional switching from a drug-activating enzyme to a drug-binding protein

Abstract: Self-protection in the mitomycin C (MC)-producing microorganism Streptomyces lavendulae includes MRD, a protein that binds MC in the presence of NADH and functions as a component of a unique drug binding-export system. Characterization of MRD revealed that it reductively transforms MC into 1,2- cis -1-hydroxy-2,7-diaminomitosene, a compound that is produced in the reductive MC activation cascade. However, the reductive reaction catalyzed by native MRD is sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This NADH requirement led to the discovery that Mrd can, in fact, act as a weak activator of 19 through the Mrd-dependent generation of 1,2-cis-1-hydroxy-2,7-diaminomitosene, a compound that is produced in the reductive 19 activation cascade. 243 The finding of a 19-activating activity appeared to be conflicting with the previously identified protective effect of Mrd. However, the reductive reaction catalyzed by Mrd is slow and results in a prolonged association of 19 and its corresponding reduced product with the protein.…”
Section: Resistance By the Producing Organismsmentioning
confidence: 86%
See 1 more Smart Citation
“…This NADH requirement led to the discovery that Mrd can, in fact, act as a weak activator of 19 through the Mrd-dependent generation of 1,2-cis-1-hydroxy-2,7-diaminomitosene, a compound that is produced in the reductive 19 activation cascade. 243 The finding of a 19-activating activity appeared to be conflicting with the previously identified protective effect of Mrd. However, the reductive reaction catalyzed by Mrd is slow and results in a prolonged association of 19 and its corresponding reduced product with the protein.…”
Section: Resistance By the Producing Organismsmentioning
confidence: 86%
“…Further characterization revealed that Mrd was able to reversibly bind and sequester 19 with no observable antibiotic modification. 243 However, Mrd was shown to require NADH to exert its protective drugbinding function. This NADH requirement led to the discovery that Mrd can, in fact, act as a weak activator of 19 through the Mrd-dependent generation of 1,2-cis-1-hydroxy-2,7-diaminomitosene, a compound that is produced in the reductive 19 activation cascade.…”
Section: Resistance By the Producing Organismsmentioning
confidence: 99%
“…In order to rationalize the intricate electronic interactions between transition metal ions and quinone redox systems in biochemical environments, there have been considerable investigations at the molecular level of metal complexes with O,O′-chelating o -quinonoid ligands, particularly in assigning the valence state distribution at the metal−quinone interface . However, despite the biochemical significance, , far fewer results have been reported for the coordination chemistry of p -quinonoid ligands, , including those with combined o , p -quinone functions. The present study is aimed at exploring the electronic structural aspects of two diastereomeric diruthenium compounds, [(acac) 2 Ru(μ-L)Ru(acac) 2 ], 1 and 2 (Scheme ), where L 2− is the two-electron-reduced p -quinonoid ligand 1,4-dioxido-2,3-bis(3,5-dimethylpyrazol-1′-yl)benzene and acac − = acetylacetonate = 2,4-pentanedionate. Although 1,4-dioxido-2,5-bis(pyrazol-1′-yl)benzene, (L′) 2− , has been used previously for the formation of polynuclear complexes, including [(bpy) 2 Ru(μ-L′)Ru(bpy) 2 ] n , the new compounds 1 and 2 represent the first set of polynuclear metal complexes bridged by L 2− .…”
Section: Introductionmentioning
confidence: 99%
“…However, para -quinones (Chart ) such as vitamin K derivatives, ubiquinones, or plastoquinones also play many important roles in energy conversion (photosynthesis, respiration) and information transfer. , …”
Section: Introductionmentioning
confidence: 99%
“…The donor substituents (O or N) at the 1,4 positions may combine with the quinone oxygen atoms to create a bis(chelate) situation with a noninnocent bridge for dimetal coordination. The combination of various accessible valence states of biochemically relevant noninnocent quinonoid systems (Q 0 = quinone, Q •– = semiquinonate, Q 2– = catecholate) and of ruthenium (Ru II , Ru III , Ru IV ) can result in complex valence and spin distribution patterns at the metal–ligand interface . Close lying and efficiently mixing frontier orbitals are responsible for this behavior, and the high degree of covalent bonding can even preclude specific oxidation state descriptions .…”
Section: Introductionmentioning
confidence: 99%